Pengaruh switching value terhadap finansial usaha kerupuk ikan cumi (Loligo sp.) di Desa Weru Kecamatan Paciran Kabupaten Lamongan - Dona Wahyuning Laily; Ika Purnamasari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Lamongan Regency is known as the largest fishery area in East Java. This will give benefit on the fishing community in terms of fishermen’s welfare. Most of the fish caught are sold directly to middlemen (tengkulak) and only few fishhermen did the increasing value in the form of processed fish or diversification of products. The purpose of this study was to analyze the financial in Weru Village, Paciran District, Lamongan Regency. This research was conducted from July to October 2020, using primary data with a syrvey method for the business of squid chips processing in Weru Village, Paciran District, Lamongan Regency. The financial feasibility of squid chips processing business is analyzed by using several investment criteria, namely Net Present Value, Internal Rate of Return, Payback Period, Net B/C Ratio. Business sensitivity is analyzed by using switching value. Based on the results of reserach, the business of manufacturing squid chips is feasible. The financial value that can be obtained is the NPV value of Rp. 80,835,098.13, IRR of 61,87 percent, net B/C of 1.81 and payback period of 3 years and 25 days. Meanwhile, the sensitivity analysis shows that the decrease in selling proce is more sensitive than the decrease in the proce of raw materials. The highest increase in the price of raw materials was 39.92 percent and [recenatge of decrease in the selling proce of squid chips with the lowest value was 21,87 percent.